EFFECTIVENESS OF NUTRITIONAL IMPROVEMENT AMONG CHILDREN WITH PICKY EATING THROUGH THE USE OF CALOKID GOLD IN SOME PRESCHOOLS IN NORTHERN MIDLAND AND MOUNTAINOUS REGION (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to evaluate the effectiveness of a special dietary food product in improving the nutritional status of children with picky eating in Thai Nguyen province.Method: Children in the intervention group received 50g of Calokid Gold supplement twice a day (equivalent to 470 kcal/day and 20 micronutrients and minerals).Results: After 3 months of intervention, the weight and height gains in the intervention group at 1, 2, and 3 months were 0.37 kg, 0.79 kg, and 1.07 kg; 0.80 cm, 1.42 cm, and 2.02 cm), respectively - significantly higher compared to the control group (0.12 kg, 0.48 kg, and 0.69 kg) and (0.59 cm, 1.09 cm, and 1.61 cm), p < 0.001. Improvements in WAZ, HAZ, and WHZ were also significantly greater in the intervention group than in the control group (p < 0.001). The prevalence of wasting and risk of wasting in the intervention group was 18.9%, significantly lower than the control group at 27.5% (p < 0.05).Conclusion: Using nutritional products effectively increases weight, height, WAZ, WHZ, and HAZ indices, reduces malnutrition rates, and lowers the risk of wasting in picky eaters.
Keywords: Picky eating, children under 5, intervention, nutrition.